Karakteristik Vegetasi Riparian dan Interaksinya dengan Kualitas Air Mata Air Sumber Awan Serta Salurannya di Kecamatan Singosari Malang - Rachmawati, Ekki Totilisa; Retnaningdyah, Catur (Biotropika: Journal of Tropical Biology, 2014)
The aims of this research are to know the characteristics of riparian vegetation based on QBR (Qualitat del Bosc de Ribera) analysis and profile of water quality (pH, DO, temperature, conductivity, turbidity) as well as to know the interaction between biotic index of the riparian vegetation and water quality in Sumber Awan Spring and its channel. Observations of riparian vegetation and water quality were conducted at seven stations. The correlation between quality of riparian vegetation and water quality was determined by Pearson correlation analysis using SPSS v.16. The results of this study indicate that the quality of riparian vegetation in the spring (station one) was the best from all downstream stations. This is indicated by the highest value of QBR (60), species richness (27 species) and species diversity index (>3). Downstream from the spring, especially five and six stations (residential area) showed lowest riparian quality, indicated by decreasing of diversity and QBR index value.The pH and DO value had fulfilled the standard for class I and class II respectivelybased on Indonesia Governmental Regulation No. 82/2001. When shrubs and tree species are high, the low value of turbidity was occurs in the water. Therefore, when the QBR score was high, the conductivity value will low in the water. Then, when pH was low, the richness of shrubs, tree species, and QBR score will high. According to QBR and water quality, Sumber Awan ecosystem was degraded. Keywords : riparian vegetation, Sumber Awan spring water, water quality